THE POWER OF THE IRRATIONAL IN POLITICS: MYTH AS A VALUE AND MOTIVATIONAL BASIS OF IDEOLOGY - Otović Višnjić, Filip (Politeia, 2024)
The text asserts the thesis that myths determine not only the foundational values of political culture and communication but also the entire cognitive perspective and its boundaries. Moreover, myths have an undisputed function in affirming political will, both in accepting the way society is organized and in radically opposing certain aspects or the totality of it. Therefore, myths, as an irrational, axiological, and motivational foundation, represent an endless source for all forms of political persuasion. They constitute the core of modern ideological systems, which rationalize myths for the reproduction of social practice. The first part of the work offers a general critique of the essential demand of Enlightenment rationalism for ’liberation’ from a mythical experience of existence. The second part presents arguments for why political myth as a phenomenon persists in modern times. The third part explains the reasons for the emergence and mechanisms of functioning of ideologies as responses to the crisis of meaning in mass, technologically structured societies.